2022
DOI: 10.1155/2022/4989344
|View full text |Cite
|
Sign up to set email alerts
|

CIMA: A Novel Classification‐Integrated Moving Average Model for Smart Lighting Intelligent Control Based on Human Presence

Abstract: Smart lighting systems utilize advanced data, control, and communication technologies and allow users to control lights in new ways. However, achieving user comfort, which should be the focus of smart lighting research, is challenging. One cause is the passive infrared (PIR) sensor that inaccurately detects human presence to control artificial lighting. We propose a novel classification-integrated moving average (CIMA) model method to solve the problem. The moving average (MA) increases the Pearson correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…This research shows that CNN has better accuracy than SVM in detecting these four activities. On the other hand, in a previous study, we found an effective CIMA method for intelligent lighting sequential classification [5]. This method predicts the presence of movement data generated by the PIR sensor.…”
Section: Related Workmentioning
confidence: 88%
See 2 more Smart Citations
“…This research shows that CNN has better accuracy than SVM in detecting these four activities. On the other hand, in a previous study, we found an effective CIMA method for intelligent lighting sequential classification [5]. This method predicts the presence of movement data generated by the PIR sensor.…”
Section: Related Workmentioning
confidence: 88%
“…CIMA is a classification of time series data case studies that utilize moving averages to increase the correlation of time series data with predicted labels [5]. The process involves several simultaneous moving average windows and Pearson correlation coefficient (PCC) analysis.…”
Section: The Cima Windowing Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…3 shows the K-fold cross-validation algorithm. K-fold cross-validation tests as many as K iterations [25]. In each iteration, the algorithm divides the data into K equal parts.…”
Section: Performance Metricsmentioning
confidence: 99%
“…Other scholars established a carbon dioxide absorption desorption process optimization system based on the product life cycle theory by using the life cycle cost method [4]. Some scholars applied the principles of supply chain environmental management and resource allocation to build a multi-stage linear solution based on single objective integer programming, solved the problem of mismatch between carbon emission peak and emission reduction benefit indicators, and achieved comprehensive energy conservation and cost reduction effect [5][6]. Therefore, based on integrated intelligence, this paper studies and discusses the optimization of the peak path of industrial carbon emissions in Shanghai.…”
Section: Introductionmentioning
confidence: 99%